A New Approach of Disaster Management in Bangladesh: Private Sector Involvement. Issue 4 (December 2014) - Izumi, Takako; Shaw, Rajib
<x xml:space="preserve">Abstract</x> Private sector involvement in disaster management is a key element to strengthening Bangladesh's future DRR capacity. Based on the interviews with various organizations and private companies, six models for the private sector in Bangladesh to develop their interests in disaster management and get involved in DRR were identified: 1) initiating DRR involvement based on corporate social responsibility (CSR) and disaster response experiences; 2) upscaling the general safety concept to include building resilience against natural disasters; 3) shifting from the subsidy‐driven to the demand‐based approach; 4) transferring from the commercial‐ to the business continuity‐oriented approach; 5) obtaining safety knowledge through technical and non‐technical training; and 6) adopting knowledge on safety and disaster management from overseas. Ultimately, this study aims to address what is necessary to strengthen the private sector involvement in Bangladesh to scale up the national DRR capacity.